College Union Dedication - Robert E. Kennedy (1971)
[00:00:07] Introduction of Cal Poly President Robert E. Kennedy [00:00:27] Kennedy addresses the audience and those who worked to open the building [00:01:38] Kennedy thanks former Cal Poly President Julian McPhee's foresight on the idea of a college union by beginning a fund from sales from the bookstore [00:03:20] Kennedy talks about how McPhee refused to spend the fund on other, more immediate projects [00:04:48] Kennedy tells the story of faith of 3 nuns who ran out of gasoline on the highway [00:06:58] Kennedy discusses how the campus has already had a College Union 'in a sense' [00:09:10] Kennedy says the key to the College Union is campus unity [00:11:45] Kennedy thanks members of the audience responsible for helping create the college union [00:13:54] Kennedy highlights that Julian McPhee did not use any state funds to finance the union [00:14:30] Kennedy talks about McPhee's faith in work and balance with play [00:16:50] Kennedy honors McPhee's philosophy of life of servitude [00:19:10] Benediction prayer [00:20:20] Conclusion of the formal ceremony